An empowerment programme to improve diet quality during pregnancy – the Power 4 a Healthy Pregnancy cluster randomised controlled trial - Renske M. van Lonkhuijzen; Jeanne H. M. de Vries; Elske Brouwer-Brolsma; Susanne Cremers; Janine P. M. Faessen; Edith J. M. Feskens; Annemarie Wagemakers (BMC Public Health)
Abstract Background A healthy diet during pregnancy is vital for the well-being of both mothers and babies. However, navigating dietary choices amidst the unique psychological and physiological changes of pregnancy can be challenging. Empowerment, defined as the ability to improve capacities, critically analyse situations, and take actions to improve them, can support pregnant women to make healthier choices. This intervention study assessed the effects of the ‘Power 4 a Healthy Pregnancy’ (P4HP) programme on diet quality and empowerment. Methods In a nonblinded, two-arm, parallel cluster randomised controlled trial, the P4HP programme was implemented in 16 randomly allocated Dutch midwifery practices, recruiting 342 participants. Participants were assigned to either the intervention (n = 186) or the control group (n = 156). The P4HP programme offered four additional consultations during pregnancy to discuss nutrition with both a midwife and dietitian, using an empowerment approach. The effectiveness of the P4HP programme was evaluated using pre- and post-intervention questionnaires assessing diet quality, empowerment, quality of life, sense of coherence, and self-rated health. The data were analysed using linear mixed models with an intention-to-treat approach. Results The P4HP programme was conducted from approximately week 11 to week 34 of pregnancy. The total diet quality score significantly improved during pregnancy in the intervention group compared to the control group (4.28; 95% CI: 1.00 to 7.56; p = 0.011), particularly driven by improvements in the scores for vitamin D, iodine, and fish. Although other components, including fruit, whole-grain foods, nuts, dairy foods, iodine, and fish showed greater average increases in diet quality scores within the intervention group, these differences were not significant. Women across all empowerment levels expressed uncertainty regarding their weight gain during pregnancy. Conclusion The P4HP programme positively influenced the dietary habits of pregnant women through empowerment. The observed improvement in diet quality underscores the potential of the P4HP programme as an effective intervention during pregnancy. This study lays the foundation for future empowerment-based interventions in maternal health contexts. Trial registration International Clinical Trial Registry Platform NL-OMON23191, date of registration: 19/05/2021.